2011
DOI: 10.1007/s00125-011-2190-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of insulin glargine on the risk of breast cancer

Abstract: Aims/hypothesis There have been growing concerns regarding the long-term effects of insulin glargine (A21Gly,B31Arg, B32Arg human insulin) on the risk of breast cancer. Methods We used the UK's General Practice Research Database (GPRD) to identify a cohort of women aged 40 years or over with type 2 diabetes, treated with insulin during 2002-2006 and followed until the first breast cancer diagnosis or 31 December 2009. After the users of insulin glargine had been matched with users of other insulins on age, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 31 publications
4
75
2
Order By: Relevance
“…In our systematic review, we also identified the lack of lag periods used and the inclusion of prevalent users as additional limitations in a few studies. One of the insulin glargine and breast cancer studies only observed an association among prevalent users of insulin after 5 or more years of use (27). This study suggests that duration of insulin use could be an effect measure modifier of the insulin glargine and breast cancer relationship and that studies with shorter follow-up may not be sufficient to observe these effects.…”
Section: Implications and Solutions To The Methodological Issuesmentioning
confidence: 67%
See 4 more Smart Citations
“…In our systematic review, we also identified the lack of lag periods used and the inclusion of prevalent users as additional limitations in a few studies. One of the insulin glargine and breast cancer studies only observed an association among prevalent users of insulin after 5 or more years of use (27). This study suggests that duration of insulin use could be an effect measure modifier of the insulin glargine and breast cancer relationship and that studies with shorter follow-up may not be sufficient to observe these effects.…”
Section: Implications and Solutions To The Methodological Issuesmentioning
confidence: 67%
“…Protopathic or detection bias could have resulted in 11 of the 19 studies because a lag period was not incorporated in the study design (6,7,(14)(15)(16)(18)(19)(20)(21)23,28). Furthermore, given the cancer latency and the time required to observe all the cancers that will occur in patients in these studies, short follow-up (defined here as ,5 years) was an issue in 16 studies, whose follow-up time (reported as mean, median, or maximum duration of follow-up) ranged from 0.9 to 4.5 years (5-8, [14][15][16][17]19,21,[23][24][25][26][27][28]. Only one of the studies observed an association between insulin glargine and breast cancer among prevalent users and after 5 years of use (HR 2.7 [95% CI 1.1-6.5]), which may highlight the importance of using a new user study design and having longer follow-up (27).…”
Section: Other Methodological Issuesmentioning
confidence: 99%
See 3 more Smart Citations